(untitled) (World Bulletin of Education and Learning, 2025)
The article provides a comprehensive scholarly analysis of the ethical and spiritual values inherent in Sufism and examines their role in shaping the moral development and cultural maturation of the nation. It explores the profound influence of Sufi teachings on the spiritual elevation of society and their contribution to both individual inner growth and social harmony. The study also conceptually distinguishes the educational objectives of Sufism from its spiritual-mystical aims, highlighting their unique characteristics. Furthermore, the practical significance of Sufi values in personal moral refinement is illustrated through an in-depth examination of the works of So‘fi Olloyor, whose writings serve as a key example of the transformative power of Sufi thought.